Studies in Guatemalan Ensifera: New Glaphyrosoma species (Orthoptera: Anostostomatidae) and additional data for other described species - Cadena-Castañeda, Oscar J.; Monzón-Sierra, José (Zootaxa, 2017)
We describe three new species in the genus Glaphyrosoma: G. magnaproctalis n. sp., G. franciscoasturiasi n. sp. and G. hectorcentenoi n. sp. We provide new data on the distribution of G. karnyi, G. beretka and G. anderi in Guatemala. We propose G. bruneri as nomen dubium and we define the status of specimens recorded as G. gracile in Guatemala and Costa Rica. We also include a species distribution map of this genus with the information available to us up to date and a key to species.